PENGARUH KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KEBIJAKAN HUTANG PERUSAHAAN: SEBUAH PERSPEKTIF AGENCY THEORY - Susilawati, R. Anastasia Endang (Jurnal Ekonomi Modernisasi, 2007)
According to agency theory (Jensen and Meckling, 1976), shareholders are called principal while the manager who runs the business is called the agent. The manager who is elected by the shareholders actually has to act on behalf of the shareholders but there are some conflict between them (agency conflict). The causes of that kind of conflict deal with the decision making related to the activity of cash flow (financing decision) and how the finance gained is invested (investment decision). The policy of optimal investment structure is not only influenced by the amount of debt and equity, but also by the percentage of share. The objects of this research are manufactures during 2005-2006. The sample consist of 49 companies. The analysis is using double linear regression. The result shows that both managerial ownership and institutional ownership have significant impact and negatively related to the company’s debt policy. The findings also show that managerial ownership and institutional ownership may reduce agency conflicts which finally minimizes yhe agency cost of debt.Future researches are expected to develop the methodology and the research variables so that the result will be more accurate. Besides, this research can be developed and widened from regional to international, so that the result will be more creative